Implementation and Management of the Intensive Care service in the interior of Ceará in times of COVID-19: An experience report (Research, Society and Development, 2024)
This study aims to report the experience regarding the implementation and management of the Intensive Care service in the interior of Ceará as a result of COVID-19, from March to August 2020. This is a descriptive study of the experience report type, where the intensive care unit was faced with a new reality of care, as well as the immediate selection and training of the multidisciplinary team. The structuring and organization of the hospitalization and patient treatment service included the incorporation of new technologies, the provision of Personal Protective Equipment, awareness about the isolation of an area that was then critical for the movement of people, the concomitant selection and training of the team that would provide care to these patients. It is noteworthy that actions aimed at continuing health education were fundamental to improving the quality of patient care, strengthening the safe practice of the growing demand for professionals to work in ICUs. This reality has highlighted some important aspects in the context of the Brazilian health team, such as the inadequate number of professionals, low salaries and inadequate working conditions. Thus, with the aim of guiding assistance provided with excellence, this study shows the importance of a service based on a scientific technical basis, the relevance of training and integration of multidisciplinary team and strengthens the perception of the need to implement and manage an evidence-based service to benefit from management tools, technologies and knowledge in the care of patients with COVID-19.